(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Sustainable health represents a new notion, which involves environmental, social, and economic aspects to promote the health of people and populations, both in the short term and within the long term. It emphasizes the need to build robust health systems capable of dealing with environmental, economic, and social issues.